Penguatan Pendidikan Peserta Didik Melalui Keterampilan 4C dengan Mengimplementasikan Pembelajaran Abad 21 dalam Pembelajaran Pendidikan Agama Islam - Siti Nurhalimah; Sindi Klaudia Selfa; Ulfi Amanda; Darul Ilmi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Education is a very important aspect in human life, because education is a way to a good future in accordance with the demands of the times, which at this time is also called the era of globalization of the development of science and technology (Science and Technology) which is growing very rapidly. In the implementation of 21st century learning, it is a way to make students not to be left behind in the flow of the times, this is where students who have 4C skills that must be developed are needed, namely: Communication, collaborative, critical thinking and problem solivng, creativity and innovation, in PAI learning, where this pie always needs renewal to keep up with the times. Education is a very important aspect in human life, because education is a way to a good future in accordance with the demands of the times, which at this time is also called the era of globalization of the development of science and technology (Science and Technology) which is growing very rapidly. In the implementation of 21st century learning, it is a way to make students not to be left behind in the flow of the times, this is where students who have 4C skills that must be developed are needed, namely: Communication, collaborative, critical thinking and problem solivng, creativity and innovation, in PAI learning, where this pie always needs renewal to keep up with the times.